2022
DOI: 10.21608/jpp.2022.158046.1161
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Correlation and some Morphological, Yield and its Components Traits in some Rice Hybrids

Abstract: Fourteen rice hybrids were grown in the two successive seasons 2020 and 2021 in Kafr El-Sheikh, Egypt, at the Experimental Farm of Rice Research and Training Center to evaluate the presence of variation for investigated traits and to estimate correlations for the studied traits with the grain yield. Every analyzed trait revealed substantial variations between hybrids, indicating a wide range of genetic variability controlling the studied traits. Grain yield (t ha -1 ) and 100-grain weight attributes with IR696… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Also, Azarpour (2013) stated that rice grain yield had significant and positive correlation with panicle weight (r = 0.96) and biological yield (r = 0.71). Arafat et al (2022) found on rice plants there is a strong positive correlation between grain yield and other yield parameters (panicle length, number of spikelets/panicle, harvest index and biological yield). The highest degree of significant positive connection was observed between the grain yield and biological yield (r = 0.730*).…”
Section: Correlation Coefficient Among Yield and Its Components And T...mentioning
confidence: 93%
“…Also, Azarpour (2013) stated that rice grain yield had significant and positive correlation with panicle weight (r = 0.96) and biological yield (r = 0.71). Arafat et al (2022) found on rice plants there is a strong positive correlation between grain yield and other yield parameters (panicle length, number of spikelets/panicle, harvest index and biological yield). The highest degree of significant positive connection was observed between the grain yield and biological yield (r = 0.730*).…”
Section: Correlation Coefficient Among Yield and Its Components And T...mentioning
confidence: 93%